2023
DOI: 10.1590/1679-78257786
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of double parallel cracks located on a hollow cylinder

Omar Mohammed Al-Moayed,
Al Emran Ismail,
Ali Kamil Kareem
et al.

Abstract: Due to the extensive usage in the industry, the structural integrity of hollow cylinders is seen as a critical goal for stakeholders. Fracture is the most common failure mode for cylinders, which occurs due to crack propagation. Cracks can be found in single or multiple forms; when numerous, crack interaction occurs, which can exacerbate pressures beyond the material's resistance. This work uses Ansys software to examine double parallel interacting surface cracks on a hollow cylinder. The stress intensity fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…It should be noted that the results obtained for a single crack previously [23][24][25][26][27] were utilized to quantify the double crack interaction via an interaction factor. Several other research works can be found elsewhere [28][29][30][31][32][33][34][35][36], and their interactions are sometimes hard to find [37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the results obtained for a single crack previously [23][24][25][26][27] were utilized to quantify the double crack interaction via an interaction factor. Several other research works can be found elsewhere [28][29][30][31][32][33][34][35][36], and their interactions are sometimes hard to find [37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%